Measuring adolescent mental health around the globe: psychometric properties of the self-report Strengths and Difficulties Questionnaire in South Africa, and comparison with UK, Australian and Chinese data. (23rd January 2017) - de Vries, P. J.; Davids, E. L.; Mathews, C.; Aarø, L. E.
Abstract : Aims: This study evaluated the psychometric properties of the Strengths and Difficulties Questionnaire Self-Report (SDQ-S) in South African adolescents, and compared findings with data from the UK, Australia and China. Methods: A sample of 3451 South African adolescents in grade 8, the first year of secondary school ( M age = 13.7 years), completed the SDQ-S in Afrikaans, English or isiXhosa. Means, group differences and internal consistency were analysed using SPSS V22, and confirmatory factor analyses were conducted using MPlus V7. Results: In the South African sample, significant gender differences were found for four of the five sub-scale means and for total difficulties, but gender differences of alpha scores were negligible. The internal consistency for the total difficulties, prosocial behaviour and emotional symptoms sub-scales were fair. UK cut-off values for caseness (set to identify the top 10% of scores in a UK sample) led to a higher proportion of South African adolescents classified in the 'abnormal' range on emotional and peer difficulties and a lower proportion classified in the 'abnormal' range for hyperactivity. South African cut-offs were therefore generated. The cross-country comparison with UK, Australian and Chinese data showed that South African adolescent boys and girls had the highest mean scores on total difficulties as well as on the subscales of emotional symptoms and conduct problems. In contrast, South African boys and girls had the lowest mean scores for hyperactivity/inattention. The UK boys and girls had the highest mean scores for hyperactivity/inattention, while the Australian sample had the highest scores for prosocial behaviours. The Chinese boys had the highest peer problem mean scores and Chinese boys and girls had the lowest means on prosocial behaviours. Confirmatory factor analyses showed significant item loadings with loadings higher than 0.40 for the emotional and prosocial behaviour sub-scales on the five-factor model, but not for all relevant items on the other three domains. Conclusions: Findings support the potential usefulness of the SDQ-S in a South African setting, but suggest that the SDQ-S should not be used with UK cut-off values, and indicate the need for further validation and standardisation work in South African adolescents. We recommend that in-country cut-offs for 'caseness' should be used for clinical purposes in South Africa, that cross-country comparisons should be made with caution, and that further examination of naturalistic clusters and factors of the SDQ should be performed in culturally and contextually diverse settings.